NATURAL DYES, ULOS WEAVING, AND SUSTAINABLE LIVELIHOODS IN MEAT VILLAGE, INDONESIA (Proceeding of SINERGY, 2026)
Natural dye utilisation in ulos weaving is increasingly positioned as a practical pathway to align cultural heritage with sustainability-oriented rural development. This study investigates the direct influence of natural dye utilisation (X1) on (i) socio-economic sustainability and local biodiversity conservation (Y) and (ii) product–village reputation as a cultural destination (Z) in Meat Village, Lake Toba Geopark, Indonesia. The research applies a mixed-method design, combining participatory observation, in-depth interviews, and a structured survey of 61 weavers across three artisan groups. Quantitative analysis is conducted using a restricted PLS-SEM model that tests only two direct relationships: X1→Y and X1→Z. The findings indicate that natural dye utilisation is strongly and positively associated with socio-economic sustainability and biodiversity conservation, and is also positively associated with destination reputation. Qualitative evidence suggests that natural dyes strengthen perceived authenticity, reinforce cultural narratives, and encourage stewardship of dye-plant resources, which together support livelihood resilience. The study highlights natural dye practice not merely as a technical substitution for synthetic dyes, but as a value mechanism connecting ecological responsibility, product differentiation, and community-based tourism readiness. The results support targeted interventions such as sustainable dye-plant management, skills upgrading, and eco-labelling to scale adoption while safeguarding local cultural and ecological assets.